1991
DOI: 10.1105/tpc.3.7.677
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the Auxin Polar Transport System in Early Stages of Arabidopsis Floral Bud Formation.

Abstract: The pin-formed mutant pinl-1, one of the Arabidopsis flower mutants, has several structural abnormalities in inflorescence axes, flowers, and leaves. In some cases, pinl-1 forms a flower with abnormal structure (wide petals, no stamens, pistil-like structure with no ovules in the ovary) at the top of inflorescence axes. In other cases, no floral buds are formed on the axes. An independently isolated allelic mutant (pinl-2) shows similar phenotypes. These mutant phenotypes are exactly the same in wild-type plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
483
1
12

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 844 publications
(509 citation statements)
references
References 7 publications
13
483
1
12
Order By: Relevance
“…The auxin transport capacity of PINs was tested both in plant and heterologous systems (Petrášek et al 2006;Yang and Murphy 2009). These results are also supported by the fact that genetic interference with PIN proteins led to reduced auxin transport and diverse developmental phenotypes (Okada et al 1991;Gälweiler et al 1998) similar to the ones observed after application of auxin transport inhibitors (Okada et al 1991;Vieten et al 2007). …”
supporting
confidence: 70%
“…The auxin transport capacity of PINs was tested both in plant and heterologous systems (Petrášek et al 2006;Yang and Murphy 2009). These results are also supported by the fact that genetic interference with PIN proteins led to reduced auxin transport and diverse developmental phenotypes (Okada et al 1991;Gälweiler et al 1998) similar to the ones observed after application of auxin transport inhibitors (Okada et al 1991;Vieten et al 2007). …”
supporting
confidence: 70%
“…Almost no auxin transport was observed when IAA was applied at the basal side of the segments in the same manner. Therefore, the 14 C-labeled IAA applied to the apical side was transported to the physiological apical-basal direction in this assay system as well as found in our previous results from a Fujix image analyzer of BAS 2000 (Fuji Photo Film Co., Ltd., Japan) [8] and from a liquid scintillation counter [13]. After incubation at 23.5°C for 18 h, a 2-mm piece of the opposite side of the segment was cut; it was placed directly into a vial containing the liquid scintillation cocktails, and then its radioactivity was determined using a liquid scintillation counter.…”
Section: Bioassay For Patmentioning
confidence: 88%
“…Following the method reported previously [8,13] with minor modifications, the system consisting of an 14 C-labeled IAA solution in the presence or absence of the test compounds in the bottom of 1.5-mL Eppendorf plastic tubes was introduced for the detection of the bioassay-derived PAT regulators. The plant extracts were placed into the bottom of the Eppendorf plastic tubes, dried in vacuo, and then dissolved with 25 μL of 1000-fold diluted 14 C-labeled IAA [ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) C)IAA with a specific activity of 55 mCi/ mmol, 0.1 mCi/mL; American Radiolabeled Chemicals, Inc., USA].…”
Section: Bioassay For Patmentioning
confidence: 99%
See 2 more Smart Citations